IMPLEMENTATION OF DSN-MUI FATWA ON SHARIA INSURANCE PRODUCTS AT PT. ASURANSI TAKAFUL PALEMBANG BRANCH - Ulil Amri; Anggita Dwi Hanum; M Iqbal (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2022)
Insurance problems do not only stop at transactions, but also at investments. Most of the insurance purchased by the public is actually insurance that contains maysir, gharar, and usury. This means that the money received from the investment received by the customer is also not maintained as halal. It is different from investing in Sharia insurance because there is a Sharia Supervisory Board which ensures that all insurance mechanisms and investment allocations do not conflict with Sharia law. Sharia Insurance Companies are entrusted by the participants to manage premiums, develop in a lawful way, provide compensation to those who experience disasters according to the contents of the agreed agreement deed, based on the characteristics of takafuli, tabarru and mudharabah.This study aims to analyze how the implementation of the DSN-MUI fatwa regarding general guidelines for sharia insurance at PT Asuransu Takaful.This study uses a Qualitative Approach that is related to phenomena that refer to the actions of economic actors, namely humans who act around economic phenomena as well as in consumption, production and distribution with all kinds of transaction derivatives and their interactions. The research results show thattabarru funds that has been collected is managed by the company on the basis of wakalah through insurance invested in various sharia investment instruments so that the funds are more productive. The results of the tabarru' investment are actually purely the rights of the participants, while the insurance company can obtain profit sharing from the investment through a tijarah contract. Companies can also benefit from wakalah bil ujrah contracts. This is in accordance with the DSN MUI fatwa No.DSN-MUI No.21/DSN-MUI/X of 2001 concerning General Guidelines for Sharia Insurance